CONSUMERACCEPTANCE OF CENDOL BY ADDITION OF CATFISH (Clarias gariepinus) FISHBONE FLOUR - Yeni Vincensia Lubis; Desmelati Desmelati; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study was aimed to determine the effect of the addition of fishbone flour of catfish in the making of cendol on consumer acceptance, todetermine the best concentration of fishbone flour of catfish in making cendol.The used method was an experimental method, with a non-factorial Completely Randomized Design (CRD) consisting of 4 levels of treatment, without adding fishbone flour (C0), adding 5% fishbone flour (C1), adding 10%fishbone flour (C2), and 15% fishbone flour (C3).The parameters used in this consumer acceptance test were organoleptic (appearance, odor, texture and flavor) and proximate analysis (moisture content, ash, protein, and calcium).The results showed that cendol with the addition of fishbone flour in C1 treatment (addition of 5% fishbone flour of catfish) was the best treatment with a consumer acceptance rate of more than 82% (> 65 panelists),with the characteristics of bright green color, pandanus odor, chewy and a slightly tasteless (non-fishy flavor). Furthermore the proximate value was 82.37% moisture content, 1.03%ash content, 1.65%protein content and 0.86%calcium content.Keywords: Cendol, fishbone flour of catfish, consumer acceptance